City Personifications and Consular Diptychs. (November 2015) - Cameron, Alan
ABSTRACT: This paper takes as its point of departure two much discussed fifth-century artifacts, an uninscribed and undated consular diptych in Halberstadt (Fig. 9), and the inscribed and (on the face of it) exactly dated consular missorium of Ardabur Aspar in Florence (Fig. 15), both hitherto presumed issued by western consuls and manufactured in western workshops. After calling into question the established criteria for distinguishing western from eastern diptychs, I propose a new set of criteria and a new date and interpretation of both objects, mainly in the light of a more comprehensive examination of the iconography of city personifications, in literature as well as art.